Treatment of Frozen Shoulder in Diabetic Patients (Journal of Pakistan Orthopaedic Association, 2015)
Objective: To check the affects of manipulation under anesthesia (MUA) and intra articular steroid injection in diabetic patients having frozen shoulder. Material and Methods: Thirty Diabetic patients having unilateral frozen shoulder with minimum duration of three months were selected for this prospective study. The patients were injected once after manipulation under anesthesia. The solution injected contained 3cc of 2% lidocain hcl (xylocain) and 2cc methylprednisolone acetate (Depomedral). All patients were advised to perform range of movements exercise daily .Follow up visits ware done at 1 week, 4 week, 8 week and 12 week for compilation of results. Results: Total of 30 patients with average age of 55 years were evaluated, out which 60% were female and 40 % were male. Right shoulder was involved in 79 %. All the active range of motion of shoulder, pain at rest as well as during motion improved considerably as compared to before the procedure. Conclusion: In diabetic patients with frozen shoulder, single MUA and intra articular injection of corticosteroid injection is effective in improving shoulder pain and disability as compared to non diabetics